Seroprevalence of Hepatitis B, Hepatitis C and Human Immunodeficiency Virus in Patients with Thalassemia Major in Zahedan, Southeast of Iran - Hosnie Hoseini (Golestan University Of Medical Sciences, 2019)
Background and objectives: Patients with thalassemia are at high risk of hepatitis B, hepatitis C, HIV infections because of the frequent and long-term need for blood transfusion. In the present study, we aimed to determine prevalence of hepatitis B virus (HBV), hepatitis C virus (HCV) and HIV in patients with thalassemia major in a hospital in Zahedan, Iran. Methods: This descriptive study was performed on 289 thalassemia major patients (130 men and 159 women) who were referred to the Ali ibn Abi Talib hospital in Zahedan, Southeast of Iran. First, serum of patients was checked for presence of antibodies against HB surface antigen, HCV and HIV by ELISA, and then results were confirmed by immunoblotting. Data were analyzed with SPSS 21 software using chi-square test. Results: Of the 289 patients, 11(3.8%) were anti-HBs positive, 11(3.8%) were anti-HCV positive, and none were positive for HIV antibodies. There was no significant difference in the prevalence of the viruses between different age groups. We found no significant correlation between history of HBV vaccination and the absence of infection with the virus in thalassemia patients. Conclusion: Although the prevalence of HCV and HBV infection is not alarmingly high in thalassemia patients in Zahedan (Southeast of Iran), screening of blood donors using more sensitive detection techniques can effectively reduce the prevalence and incidence of these viral infections in this area.